Analysis of Total Hardness Levels in Water Around the Trunojoyo Campus using the Complexometric Method - Mubarok, Ibnul; Putri, Nuraida Ameliana (Universitas Nusa Cendana, 2025)
Water hardness, primarily caused by dissolved calcium (Ca²⁺) and magnesium (Mg²⁺) ions, affects the suitability of groundwater for domestic use and may have adverse health and operational effects when concentrations are high. Indonesia’s clean water quality standard (PERMENKES No. 492/MENKES/PER/IV/2010) sets a maximum hardness of 500 mg/L as CaCO₃. This study determined the total hardness of well water in three villages surrounding the Universitas Trunojoyo Madura campus (Telang, Gili Timur, and Labang) using complexometric titration with 0.01 M EDTA. Samples were collected by simple random sampling and titrated in triplicate. Results showed pronounced spatial variation: Telang village exhibited very high total hardness average 715.7 mg/L, Gili Timur had moderate hardness 146 mg/L, and Labang had low hardness 101.3 mg/L. The elevated hardness in Telang exceeds the national standard and likely reflects local geology (limestone contact and calcareous soils). We recommend pretreatment of well water used for drinking in areas with very high hardness.